Gasparee from the Mainland, Trinidad, B.W.I. - (:unkn) unknown (Cannings and Co., Ltd., [Trinidad], 2011)
The postcard shows a view from mainland Trinidad of Gasparee Island which lies off Trinidad's north west coast and Chaguaramas Bay.
Colour: Hues of green; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Gaspar Grande; Gasparee